Valency-Increasing Mechanism in the Dawan Language - Naniana N. Benu; Risman Iye; I Wayan Simpen; Fithriyah Inda Nur Abida (SUAR BETANG, 2022)
This article discusses the valency-increasing mechanism in the Dawan language. The data was obtained through observation of Dawan language speakers by applying the note-taking method. Other data were obtained from literature in Dawan's language, namely Beno Alekot (bible) and Si Knino (songbook). In addition, the data is supported by intuitive data from the researcher as a native speaker of the Dawan language. Considering the variety of dialects in this language, the data and discussion are focused on the Amanuban dialect. The results show that the mechanism of valency-increasing in the Dawan language is a transitive process. This process is carried out through the strategy of adding new arguments such as in causative construction or promoting peripheral arguments into core arguments as in applicative construction. The transitive referred to is the process of making an intransitive clause into a transitive or a transitive into a ditransitive. This process does not cause morphological changes to the verb as the core of a clause.AbstrakArtikel ini membahas mekanisme peningkatan valensi dalam bahasa Dawan. Data diperoleh melalui observasi terhadap penutur bahasa Dawan dengan menerapkan metode simak dan catat. Data lain diperoleh dari literatur berbahasa Dawan, yaitu Beno Alekot (Alkitab) dan Si Knino (buku nyanyian). Selain itu, data tersebut didukung oleh data intuitif dari peneliti sebagai penutur asli bahasa Dawan. Mengingat keragaman dialek bahasa ini, data dan pembahasan difokuskan pada dialek Amanuban. Hasil analisis data menunjukkan bahwa mekanisme peningkatan valensi dalam bahasa Dawan merupakan proses transitif. Proses itu dilakukan melalui strategi penambahan argumen baru seperti pada konstruksi kausatif atau menempatkan argumen periferal ke dalam argumen inti seperti pada konstruksi aplikatif. Transitif yang dimaksud adalah proses menjadikan klausa intransitif menjadi transitif atau transitif menjadi ditransitif. Proses itu tidak menyebabkan perubahan morfologis pada verba sebagai inti dari sebuah klausa.